Deep dynamics - Nils Gottfries; Glenn Mickelsson; Karolina Stadin (Uppsala University, Department of Economics, 2018)
Combining micro and macro data, we construct demand-side shocks, which we take to be exogenous for individual firms. We estimate a reduced-form model to describe how firms adjust their production, employment, capital stock, and inventories in response to such shocks. Then, we chose the structural parameters of a theoretical model so that the theoretical model can match the impulse-response functions from the estimated reduced-form model. Firms' reactions to demand-side shocks are well explained by a model where firms have modest market power, face convex adjustment costs and where they can vary utilization flexibly. The stock-out motive helps to explain inventory dynamics.
urn:nbn:se:uu:diva-354578
Keywords: E22; E23; E24; E32; 330; capacity utilization; production factor; labor hoarding; labor productivity; inventory holdings; returns to scale; production function; Solow residual